Barriers to male transmission of mitochondrial DNA in sperm development. - Deluca, S.Z.; O'Farrell, P.H. (Developmental Cell, 2012)
Across the eukaryotic phylogeny, offspring usually inherit their mitochondrial genome from only one of two parents: in animals, the female. Although mechanisms that eliminate paternally derived mitochondria from the zygote have been sought, the developmental stage at which paternal transmission of mitochondrial DNA is restricted is unknown in most animals. Here, we show that the mitochondria of mature Drosophila sperm lack DNA, and we uncover two processes that eliminate mitochondrial DNA during spermatogenesis. Visualization of mitochondrial DNA nucleoids revealed their abrupt disappearance from developing spermatids in a process requiring the mitochondrial nuclease, Endonuclease G. In Endonuclease G mutants, persisting nucleoids are swept out of spermatids by a cellular remodeling process that trims and shapes spermatid tails. Our results show that mitochondrial DNA is eliminated during spermatogenesis, thereby removing the capacity of sperm to transmit the mitochondrial genome to the next generation.